Both total and phosphorylated tau are increased in Alzheimer's disease. Issue 5 (1st May 2001) - Sjögren, M; Davidsson, P; Tullberg, M; Minthon, L; Wallin, A; Wikkelso, C; Granérus, A-K; Vanderstichele, H; Vanmechelen, E; Blennow, K
Abstract : BACKROUND: Pathological tau protein concentrations in CSF are found in both Alzheimer's disease (AD) and frontotemporal dementia (FTD), but studies on brain tissue have suggested that the tau pathology in AD differs from that in FTD and that the difference may be related to the degree of phosphorylation. As CSF tau protein is increased after stroke, tau may also be implicated in the pathophysiology of vascular dementia, of which subcortical arteriosclerotic encephalopathy (SAE) is a putative subtype. OBJECTIVES: To investigate the nature of tau protein in CSF and the involvement of total CSF tau and phosphorylated CSF tau (phosphotau) in various types of dementia. METHODS: Using ELISAs for total tau and tau phosphorylated at Thr181 (phosphotau), the CSF concentrations of total tau and phosphotau were determined in patients with probable and possible AD (n=41 and 19, respectively), FTD (n=18), SAE (n=17), and Parkinson's disease (PD; n=15) and in age matched controls (n=17). All the antibodies stained the lower molecular weight bands, whereas only the antibodies that recognise phosphorylated tau stained the higher molecular bands. RESULTS: Both CSF tau and CSF phosphotau were increased in probable AD compared with FTD (p<0.001), SAE (p<0.001), PD (p<0.001), and controls (p<0.001). CSF phosphotau was increased in possible AD compared with FTD (p<0.001) and SAE (p<0.001). CSF tau and CSF phosphotau were positively correlated in all the groups. Molecular weight forms of tau ranging from 25 kDa to 80 kDa were found in the CSF CONCLUSION: Both phosphorylated and unphosphorylated tau isoforms were present in the CSF, and tau protein appeared in both truncated and full length forms. The results suggest that the CSF concentrations of tau and phosphotau are increased in about two thirds of patients with probable AD and in half of those with possible AD but are normal in FTD, SAE, and PD compared with normal aging. Values in the normal range do not exclude AD.